EXAMINING OF SEVERAL HIDROPONICS NUTRIENTS FOR LETTUCE ON MODIFIED FLOATING SYSTEM HIDROPONIC TECHNOLOGY - Siregar, Jureni (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2015)
This research aimed to find out the best nutrition for lettuce cultivated in a modified floating system hydroponictechnology. Experimentused inthis researchwas Randomized Complete Block (RBC)with factorial arrangement.Single factor treatments were five different brand nutrients (N1, N2, N3, N4, and N5), each consisted of fivereplicates. Data was analyzed by using Analysis of Variance (ANOVA), followed by Least Significant Difference(LSD)multiple comparasion5%. The result showed that the better nutritions for lettucewasGoodplant (N1) andNutri Mix (N5). Were indicated by the better performance of all parameters measured, such as plant height,number of leaves, root length, biomassweight with upper part and lower part.Keyword : Lettuce,Modified floating systemhydroponic technology,Nutrition.